Grow through what you go through - Ortiz, Chelsea L. (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
Being a millennial person-of-color in the twenty-first century is exhaustive in itself—adding the vulnerabilities of a global pandemic magnified that undertaking. As women, we bear the responsibilities of balancing our professional life with our family life; our role as a partner or friend with our role as an individual being; and our mental health with our social health. “Grow Through What You Go Through” explores the value of saying “Yes, I can do this too” when COVID-19 gave many a reason to say, “I’ve had enough.” Between being a supportive partner and family member to many who experienced financial and educational setbacks and being an important part of preparing the next set of future nurses to lead and excel during a global pandemic, COVID-19 enlightened my perspective on who I was at the start of COVID-19 and the person I would turn out to be by the end of it.
Keywords: COVID-19; Coping; Resilience; dept.nur